Psychological Well-Being A Housewifes Who Have Children with Special Needs : Psychological Well-Being pada Ibu Rumah Tangga yang Memiliki Anak Berkebutuhan Khusus - Berliana Putri Pertiwi Putri; Ramon Ananda Paryontri (Academia Open, 2022)
Housewives have a big role in the process of child development. So that mothers must be understand and find out about the conditions and needs of their children, especially in taking care of children with special needs (Special Needs Children).This research is a qualitative research with a phenomenological approach. The data collection technique used is the interview method. This study uses 3 subjects as sources of information in extracting data, plus 3 secondary subjects. The data collection technique used is the snowball sampling technique which will meet the criteria: 1) housewives who do not work, and 2) aged 30-40 years old. The results of the research that have been obtained state that the three subjects have psychological well-being based on aspects and factors of the psychological well-being. There are other influences that support the psychological well-being of the subject, gratitude, self-adjustment, self-concept, and regulations that exist in the three subjects. Highlights: The role of housewives in child development, especially for children with special needs. Qualitative research with a phenomenological approach and interview method for data collection. Psychological well-being of housewives, including factors such as gratitude, self-adjustment, self-concept, and regulations. Keywords: Housewives, Child development, Special needs children, Qualitative research, Psychological well-being